2007
DOI: 10.1021/ic062274e
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Fluorescent Probe for Selective Detection of Hg2+ in DMF Aqueous Media

Abstract: A highly sensitive fluorescent probe 1 for selective detection of Hg ion in mixed N,N-dimethylformamide aqueous media was designed and prepared by incorporating the well-known Rhodamine 6G fluorophore and a carbohydrazone binding unit into one molecule. The fluorescent probe 1 can detect the parts per billion level of HgII in a mixed aqueous environment and displays a highly selective response of fluorescence enhancement toward HgII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(150 citation statements)
references
References 26 publications
7
143
0
Order By: Relevance
“…Herein, we are reporting the novel rhodamine based chemodosimeter rhodamine B phenyl hydrazide for Cu 2 þ ions which contains reactive phenyl hydrazide group [39]. Due to the presence of reactive phenyl hydrazide group the probe exhibits above said silent features like specific irreversible "turn-on" absorbance/fluorescence changes with Cu 2 þ ions in the pH range 1-6 and the absorbance/emission wave lengths (550/580 nm) are longer compared to some of the reported probes [34][35][36]. The probe also has higher quantum yields compare to the reported rhodamine probes [30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Herein, we are reporting the novel rhodamine based chemodosimeter rhodamine B phenyl hydrazide for Cu 2 þ ions which contains reactive phenyl hydrazide group [39]. Due to the presence of reactive phenyl hydrazide group the probe exhibits above said silent features like specific irreversible "turn-on" absorbance/fluorescence changes with Cu 2 þ ions in the pH range 1-6 and the absorbance/emission wave lengths (550/580 nm) are longer compared to some of the reported probes [34][35][36]. The probe also has higher quantum yields compare to the reported rhodamine probes [30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 98%
“…One of the chemodosimeter based on rhodamine derivative have been reported for imaging Cu 2 þ in living HeLa cells with high sensitivity and fast response time but this probe cannot distinctly recognize Cu 2 þ from Hg 2 þ , and thereby, is not suitable for monitoring the concentration of copper ions in complicated cellular environment [33]. Recently two fluorescent rhodamine derivatives were reported for Cu 2 þ ions but they posse's comparatively short emission wavelengths [34][35][36]. The short emission wavelength probes are disadvantageous for cell imaging because the cells have to irradiate with high energy radiations which lead to the cell toxicity [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…5), containing rhodamine 6G fluorophore and a carbohydrazone binding unit, for selective detection of Hg 2+ ion in mixed DMF aqueous media. 15 The fluorescent probe 6 can detect the parts per billion level of Hg 2+ in a mixed aqueous environment and displays a highly selective response of fluorescence enhancement toward Hg 2+ . X-ray structural analysis of compound 6-Hg 2+ confirmed the formation of a 1:2 metal/ligand complex.…”
Section: +mentioning
confidence: 99%
“…The rhodamine groups were present in the form of a ring-opened amide conformation to indicate the delocalized xanthene moiety, which showed long wavelength absorption and fluorescence enhancement. 15 Simultaneously, a highly selective and multisignaling optical-electrochemical chemosensor 7 (Fig. 6) for Hg 2+ based on a rhodamine dye bearing both a ferrocenyl group and an 8-hydroxyquinoline moiety was designed and prepared by Yang et al 16 Compound 7 displayed a selective fluorescence enhancement, colorimetric change (colorless to pink) and an obvious change in its reversible ferrocene/ferricinium redox cycles in the absence and presence of Hg .…”
Section: +mentioning
confidence: 99%
“…6 Rhodamine 6G derivative, which has a carbohydrazone binding unit, exhibits selective Hg 2+ ion signaling by ring opening of the lactam moiety. 7 Chemodosimetric determination of Hg 2+ ions in aqueous media has been accomplished using an irreversible desulfurization reaction of a thiosemicarbazide derivative of fluorescein to its corresponding oxadiazole, with efficient chromogenic and fluorogenic signaling. 8 More recently, Zheng et al reported an interesting finding that the Cu 2+ -selective signaling behavior of hydrazide 1 could be effectively switched to Hg 2+ selectivity by replacing one oxygen atom of the spirolactam with a sulfur atom to yield a thiohydrazide.…”
Section: Introductionmentioning
confidence: 99%